Casting a nanofiltration polymer membrane for water softening - Wong, Miao Ling. (2009)
Potable water is essential for survival of all forms of lives. However, only a small percentage of water is available for consumption without going through water treatment process. Water hardness is one of the parameters which must take into considerations when concerning water quality. Dissolved Magnesium and Calcium ions in water are the main contributors to hard water’s characteristics. Hard water can pose several problems to users and is definitely undesirable. Thus, the author aims to investigate low cost and improved methods for water softening through casting of nanofiltration membranes as well as testing commercially available nanofiltration membrane. The ultimate outcome is the high reduction of Calcium Carbonate content in hard water. In this project, 13 experiments were carried out. The author used two types of membranes, namely, Polyacrylonitrile (PAN) 10 ultrafiltration membrane and Polytetrafluoroethylene (PTFE) coated fiber glass cloth (a nanofiltration membrane). This was done so as to compare the performance of the commercially made nanofiltration membrane with the self cast nanofiltration membranes. Out of the 13 experiments conducted, 12 of them were tested through the casting of the nanofiltration layer on the commercially bought PAN 10 ultrafiltration membrane. The membrane has an asymmetric porous structure which is used as the support for the thin active layer. Consistency in the usage of same support membrane will ensure constant performance of the backing material. The materials and their concentrations used for the thin layer were varied. The fabrication technique applied for casting the thin film is interfacial polymerization. The desired properties for the support membrane are high mechanical strength and uniform porous structures. As for the thin film, high selectivity is desired. On the contrary, the PTFE coated fiber glass cloth was tested in one experiment. PTFE coated fiber glass cloth has a remarkably low coefficient of friction, heat and chemical resistance. The results have shown that better salt rejection rate was achieved when the i) transmembrane pressure is higher, ii) concentrations of the aqueous and organic phase solutions are increased and iii) thickness of the nanofiltration layer is increased. On the other hand, higher salt rejection rate is accompanied by the decrease in flux rate. Besides carrying out the experiment to test for the rejection rate and flux rate, surface characterization of membranes was also performed. Scanning Electron Microscope (SEM) and Atomic Force Microscope (AFM) were used to view the microscopic structures of the membranes’ surfaces as well as their cross sections. These allowed the author to have a better understanding of the membranes’ characteristics.